'Candidatus Phytoplasma sacchari', a novel taxon - associated with Sugarcane Grassy Shoot (SCGS) disease. Issue 1 (8th January 2021) - Kirdat, Kiran; Tiwarekar, Bhavesh; Thorat, Vipool; Sathe, Shivaji; Shouche, Yogesh; Yadav, Amit
Abstract : Sugarcane Grassy Shoot (SCGS) disease is known to be related to Rice Yellow Dwarf (RYD) phytoplasmas (16SrXI-B group) which are found predominantly in sugarcane growing areas of the Indian subcontinent and South-East Asia. The 16S rRNA gene sequences of SCGS phytoplasma strains belonging to the 16SrXI-B group share 98.07 % similarity with ' Ca . Phytoplasma cynodontis' strain BGWL-C1 followed by 97.65 % similarity with ' Ca . P. oryzae' strain RYD-J. Being placed distinctly away from both the phylogenetically related species, the taxonomic identity of SCGS phytoplasma is unclear and confusing. We attempted to resolve the phylogenetic positions of SCGS phytoplasma based on the phylogenetic analysis of 16S rRNA gene (>1500 bp), nine housekeeping genes (>3500 aa), core genome phylogeny (>10 000 aa) and OGRI values. The draft genome sequences of SCGS phytoplasma (strain SCGS) and Bermuda Grass White leaf (BGWL) phytoplasma (strain LW01), closely related to ' Ca . P. cynodontis', were obtained. The SCGS genome was comprised of 29 scaffolds corresponding to 505 173 bp while LW01 assembly contained 21 scaffolds corresponding to 483 935 bp with the fold coverages over 330× and completeness over 90 % for both the genomes. The G+C content of SCGS was 19.86 % while that of LW01 was 20.46 %. The orthoANI values for the strain SCGS against strains LW01 was 79.42 %, and dDDH values were 22. Overall analysis reveals that SCGS phytoplasma forms a distant clade in RYD group of phytoplasmas. Based on phylogenetic analyses and OGRI values obtained from the genome sequences, a novel taxon ' Candidatus Phytoplasma sacchari' is proposed.